Implementasi Metode Lean Service dan 5S untuk Meningkatkan Efisiensi Waktu Pelayanan di Dinas Pencegah dan Pemadam Kebakaran Kota Medan - Tarigan, Uni Pratama Pebrina; Budiman, Irwan (TALENTA Publisher, 2021)
Fire is a threat to human safety. With the rapid development and progress of development, the risk of fire is increasing. The population is getting denser, the construction of office buildings, residential areas, and industries that are increasingly developing so that these areas have a level of vulnerability to the risk of fire. Therefore, the existence of the Fire Prevention and Fire Service is needed. The problem that often occurs is the length of time the Fire Prevention and Fire Department gets to the scene of the fire. This causes huge losses to the community both in funds and lives. This study’s purpose is to improve the efficiency of service time at the Fire Prevention and Department of the Fire so that losses due to fire can be minimized. The method used is Lean Service and for the design using the 5S method. The results of this paper that the value added activity amount 37%, while the non-value added activity amount 63%. These results indicate the need for a reduction in activity so that processing time is more efficient. The result of this analysis using Fishbone Diagram and FMEA, it was found that the most cause of the highest failure mode was activity in the storage area for equipment and personal protective equipment that was difficult to reach and irregular so that the best layout was designed using the 5S Method.